Diversification of Maggot Derivative Products in the Kompas Lestari Program in Makartitama Village, Paninjauan Regency, South Sumatra - Amalia, Richa; Putra, Erwin Hendra; Suharyadi (International Journal of Social Science and Community Service, 2024)
The success of the Waste Bank in reducing organic and inorganic waste in Makartitama Village, OKU, has inspired PT Pertamina Hulu Energi Ogan Komering to develop the Sustainable Waste Management Group Sinergi PHE Ogan Komering (KOMPAS LESTARI). The primary focus of this program is to utilize organic waste for cultivating Black Soldier Fly (BSF) maggots, which are then used in the production of pellets or alternative fish feed for freshwater aquaculture and liquid organic fertilizer for organic vegetable cultivation. In 2023, the BSF-based products, initially used by the beneficiary groups of Kompas Lestari, are being developed for commercialization. In its third year, Kompas Lestari is embarking on a business incubation phase for processed maggot products. This phase includes training in product diversification, marketing strategies, and registration for Home Industry Food (P-IRT).